Tax Exemptions in Montreal and Toronto, 1870 to 1920 - Levine, Gregory (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1991)
Informed by an historical materialist perspective tempered by an appreciation of the impact of religious institutions on class formations, this paper charts and explains debates over tax exemptions in Montréal and Toronto, from 1870 to 1920. Local taxation was an important part of the revenue source for these two great cities, in this important period in Canadian urbanization. Debates over exemption from taxation constitute an appraisal of the way the local state was to marshall resources. This paper explains these struggles through an understanding of the interplay of class and religion within the political and cultural geographies of Montréal and Toronto.